2018
DOI: 10.1038/s41467-018-07651-7
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular-clustered facial amphiphilic antimicrobials

Abstract: Bacterial infections and antibiotic resistance, particularly by Gram-negative pathogens, have become a global healthcare crisis. We report the design of a class of cationic antimicrobial polymers that cluster local facial amphiphilicity from repeating units to enhance interactions with bacterial membranes without requiring a globally conformational arrangement associated with highly unfavorable entropic loss. This concept of macromolecular architectures is demonstrated with a series of multicyclic natural prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 60 publications
2
147
0
1
Order By: Relevance
“…Confocal laser scanning microscopy (CLSM) was used to visualize the damaged membranes of bacteria after LYZOX treatment [28]. LYZOX solution (2,000 μg/mL) in saline was prepared and adjusted to pH 7.0–7.1 by adding 60 μL of 1.0 M phosphate buffer (pH 7.2) per 1.0 mL solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal laser scanning microscopy (CLSM) was used to visualize the damaged membranes of bacteria after LYZOX treatment [28]. LYZOX solution (2,000 μg/mL) in saline was prepared and adjusted to pH 7.0–7.1 by adding 60 μL of 1.0 M phosphate buffer (pH 7.2) per 1.0 mL solution.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 750 μL of each sample was added to 750 μL of PBS, and 750 μL of control (positive or negative control) was added to 750 μL of each corresponding concentration of LYZOX because the absorbances of LYZOX at 545 nm were different at each concentration. Each OD was measured at 545 nm to calculate the hemolysis rate by using the following equation: Hemolytic rate (HR) = (Absorbance of sample [AS]–Absorbance of negative control with the corresponding concentration of LYZOX [AN]) / (Absorbance of positive control with the corresponding concentration of LYZOX [AP]–AN) [28, 33]. AS, AN, and AP are the OD values of the adjusted supernatants from the test samples, the negative control and the positive control, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these differences in cell walls play a crucial role in the susceptibility of microbes to cationic polymers. Typically, Gram-negative and fungi are more difficult to eliminate than Gram-positive [9], but contrary behaviors have been proven for some cationic polymeric systems [10] and broad-spectrum antimicrobial polymers have also been developed [11][12][13]. Some studies concluded that cationic charge influences more the interaction with the bacterial membrane of Gram-positive bacteria in comparison with Gram-negative bacteria, while the hydrophobicity and amphiphilic balance of the polymers affects more the efficacy against Gram-negative bacteria [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Chain transfer agent 2‐cyano‐2‐propyl benzodithioate (97%, CPB) was purchased from Sigma‐Aldrich and used directly. Monomer 2‐cobaltocenium amidoethyl methacrylate hexafluorophosphate (CoAEMAPF 6 ) was synthesized by reacting cobaltocenium monocarboxylic acid with 2‐aminoethyl methacrylate hydrochloride in the presence of coupling agent N ‐(3‐(dimethylamino)propyl)‐ N ′‐ethylcarbodiimide (EDC) according to established methods . 2‐Aminoethyl methacrylate hydrochloride (90%), N ‐(3‐dimethylaminopropyl)‐ N′ ‐ethylcarbodi imide hydrochloride (EDC‐HCl, 98%), 4‐(dimethylamino)pyridine and tetrabutylammonium chloride (TBACl) were purchased from Sigma‐Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%